A Snapback-Free and Low Turn-Off Loss 15 kV 4H–SiC IGBT with Multifunctional P-Floating Layer - Xiaodong Zhang; Pei Shen; Zhijie Zou; Mingxin Song; Linlin Zhang (Micromachines, 2022)
In this paper, a 4H–SiC IGBT with a multifunctional P-floating layer (MP-IGBT) is proposed and investigated by Silvaco TCAD simulations. Compared with the conventional 4H–SiC field stop IGBT (FS-IGBT), the MP-IGBT structure features a P-floating layer structure under the N-buffer layer. The P-floating layer increases the distributed path resistance below the buffer layer to eliminate the snapback phenomenon. In addition, the P-floating layer acts as an amplifying stage for the hole currents’ injection. The snapback-free structure features a half-cell pitch of 10 μm. For the same forward voltage drop, the turn-off loss of the MP-IGBT structure is reduced by 42%.